Experimental and Theoretical Study on Lipophilicity of Synthetic 1,2-Dithiole-3-thiones - Rahmani, Z.; Saidi, M.; Yousfi, M.; Dakmouche, M. (Asian Journal of Chemistry, 2013)
The aim of this work is to determine the partition coefficients log Pwo of eleven compounds including dithiolethiones, dithiolone, nitrone, 1,2-dithiole-3-imine and compounds which is carried out by two experimental methods i.e., UV-visible and HPLC. According to the procedure of the traditional method shake-flask and we confirm the results by using a theoretical method for calculating the values of log Pwo. The other part of this study is to obtain the value of the unknown fragmental constant of imine(C=N) and the value found of imine fC=N underlined in the calculatation of log Pwo (N-p-nitrophenyl 5-phenyl-1,2-dithiole-3-imine); then to compare the calculated log Pwo value with the experimental study. The results show that: (i) the dithiolones are more hydrophilic than the dithiolethiones; (ii) the values of log Pwo of derivatives bromines, imine and nitrone are lately given in experiments. Our analysis demonstrates good agreement between the experimentally observed and calculated log Pwo values.